2000
DOI: 10.1046/j.1365-2222.2000.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Late onset reactions to oral food challenge are linked to low serum interleukin‐10 concentrations in patients with atopic dermatitis and food allergy

Abstract: These results indicate that oral allergen challenge in atopic patients with food allergy triggers systemic release of IL-10. Patients with late onset reactions were found to have lower serum IL-10 concentrations than their immediate-reacting counterparts. Considering that IL-10 is an inhibitory cytokine of delayed-type hypersensitivity, low IL-10 in late-reacting patients may explain the high frequency of their positive skin patch tests combined with negative skin prick tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The results of the present investigation are consistent with the consensus of the published literature that the sandwich ELISA fails to detect interferon-g in the blood of the healthy laboratory mouse (for example, Cowdery et al 1996;Mukherjee & Talwar, 1996;Halford et al 1998;Faggioni et al 2000;Sass et al 2002) or human subjects (for example, Gonzalez-Quintela et al 1999;Verbon et al 1999;Sutas et al 2000;Yoshizawa et al 2002). Previous attempts to quantify murine blood serum interferon-g bioactivity were based on inhibition of a viral cytopathic effect in vitro and also failed to detect the cytokine (Solis-Pereyra et al 1997).…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present investigation are consistent with the consensus of the published literature that the sandwich ELISA fails to detect interferon-g in the blood of the healthy laboratory mouse (for example, Cowdery et al 1996;Mukherjee & Talwar, 1996;Halford et al 1998;Faggioni et al 2000;Sass et al 2002) or human subjects (for example, Gonzalez-Quintela et al 1999;Verbon et al 1999;Sutas et al 2000;Yoshizawa et al 2002). Previous attempts to quantify murine blood serum interferon-g bioactivity were based on inhibition of a viral cytopathic effect in vitro and also failed to detect the cytokine (Solis-Pereyra et al 1997).…”
Section: Discussionsupporting
confidence: 90%
“… 2 , 3 , 7 , 8 , 9 Further, if patch tests are useful in detecting allergic contact dermatitis to foods, they are not consistently positive in other forms of delayed reactions to foods. 13 Given that no standardized form of skin testing exists for food-induced delayed systemic reactions in nonatopic individuals, and given the positive delayed reading of skin prick results in our patient but not in controls, we suggest that delayed reading of prick results with raw food may be useful in confirming the diagnosis of SD.…”
Section: Discussionmentioning
confidence: 56%
“…However, 38% of the patients with a positive challenge to cow's milk did not react in skin testing or by RAST. Sütas et al reported that in AD patients with food allergy oral challenge triggers systemic release of interleukin (IL)‐10, and subjects with late‐onset reactions have lower serum IL‐10 concentrations than their immediate‐reacting counterparts (27). Considering that IL‐10 is an inhibitory cytokine of delayed type hypersensitivity, low IL‐10 levels in late‐reacting patients may explain their high frequency of positive APTs combined with negative SPTs.…”
Section: Discussionmentioning
confidence: 99%